Civilization In Islamic Law Perspective - Hijrah, Hijrah (International Conference on Islamic Studies, 2020)
According to the history of Islamic Law development, Civilization underwent the decadences. It can be proved in it’s application of Islamic law In the human or moesleem’s life. We know that Prohet Muhammad’s period was the best period of all periods in the Islam history. After that, the periods of Khulafa’urrasyidin, and the others until nowdays. In Islamic law perspective, civilizaation undergwent the steps of decadences. It was caused by the spread of Islam in many different countries and different human’s brains. This articel is a library research by using the history approach. This article had conclude that civilization has undergone the decadences because of three things. First, because of the bad application of Islamic law. Second, because of many different thoughts in Islamic law. Third, because of different culture and human around the world. In the other sides of civilizaation, we know that Islam had developed and had been progress. But, in Islamic law, it didn’t give a good progress in civilization. And it is compared with the civilization nowdays in many countries, one of them is Indonsia as an example. Now we have many Islamic law institutions in our country as a judiciary, such as Relegion courts. These courts spread to all over regions in Indonesia. And we have Islamic law number 01 in 1974 about the merriage, the Compilation of Islamic Law n (KHI), the basic Indonesian law (UUD) 1945 pasal 29th about The Nation base on an almighty deuty, The law Number 07 in 1989 about judiciary, The law number 38 in 1999 about Zakat, the law numer 13 in 2008 about hajj organizing, and the law number 20 about National Education System pasal 20th about Religion Education. But all of those laws are not the sign of civilization progress in Islamic law. Because we are not only looking to the building and formalization of the laws, but also we look in to the application and the effectiveness of those laws and those institutions. And although in the prohet’s period didn’t have law institution but He could solve all of his societies problems in law. But nowdays, we can see that the beautiful law building can not solve societies problems perfectly.